Two Men with Advanced Amyotrophic Lateral Sclerosis Operate a Computer-Aided Television System through Mouth or Throat Microswitches. Issue 3 (June 2014) - Lancioni, Giulio E.; Ferlisi, Gabriele; Zullo, Valeria; Settembre, Manuela F.; O'Reilly, Mark F.; Singh, Nirbhay N.; Sigafoos, Jeff
This study assessed a simple technology to enable two men affected by amyotrophic lateral sclerosis, in an advanced stage (i.e., with pervasive motor disabilities and lack of speech), to operate a computer-aided television system. The technology included microswitches, a portable computer, an interface connecting the microswitches to the computer, a commercial software package to allow the possibility of watching television via computer, and specific software to allow microswitch activations to be recorded as forward commands for channel change. The participants (a) gained control over the television programs to watch or not to watch (i.e., through channel changes) and (b) showed increased attention to the programs (i.e., an increase in their watching time). The practical relevance of the findings, the integration of the technology used in this study within the participants' wider recreation and communication program, and ways of extending the research were discussed.